2010
DOI: 10.4995/wrs.2007.596
|View full text |Cite
|
Sign up to set email alerts
|

Effect of dietary sodium on digestibility of nutrients and performance in growing rabbits.

Abstract: The effects of a reduction in the sodium content from 2.6 to 1.6 g/kg DM in diets with similar electrolyte balance on fattening performances and ileal apparent digestibility of nutrients were investigated in early weaned rabbits. Two diets containing 17.9% DM of crude protein, with the same composition and only differing in sodium chloride content (0.5 and 0.2%) were given to rabbits weaned at 25 days to measure fattening performance (46 rabbits per diet), and apparent ileal digestibility (AID, 14 rabbits per … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2016
2016
2017
2017

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 15 publications
0
1
0
Order By: Relevance
“…A deficit in Na+ may impair the efficiency of digestive processes and/or the absorption of amino acids. Chamorro et al (2007) observed that a reduction in Na+ from 2.6 to 1.6 g kg−1impaired ileal digestibility of methionine and cystine, although dry matter and protein digestibility were not affected.Excess Na+ in the feed (>8-10 kg sodium chloride (NaCl) kg−1 diet) or the presence of salt in the drinking water (3000 mg kg−1) is detrimental to growth (Marai et al, 2005).…”
Section: Sodium (Na)mentioning
confidence: 92%
“…A deficit in Na+ may impair the efficiency of digestive processes and/or the absorption of amino acids. Chamorro et al (2007) observed that a reduction in Na+ from 2.6 to 1.6 g kg−1impaired ileal digestibility of methionine and cystine, although dry matter and protein digestibility were not affected.Excess Na+ in the feed (>8-10 kg sodium chloride (NaCl) kg−1 diet) or the presence of salt in the drinking water (3000 mg kg−1) is detrimental to growth (Marai et al, 2005).…”
Section: Sodium (Na)mentioning
confidence: 92%